A Sensitive Electrochemical Sensor for Rapid Determination of Mebeverine Hydrochloride and Metronidazole Benzoate Selective Molecular Imprinted Polymer in the PVC Membrane - Al Khafaji, Inas Hasan Mohammed; Al-Bayati, Yehya Kamal Khaleel (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
By using precipitation polymerization, liquid electrodes of polymers imprinted with Mebeverine hydrochloride and metronidazole benzoate were created whereas the imprinted polymer (MIP) and non imprinted (NIP) polymers were prepared by using Mebeverine hydrochloride and Metronidazole benzoate qua a template. In the polymerization process, 2-Acrylamido-2-methyl-1-propane Sulphonic acid (AMPS) or 1-Vinylimidazole (VIZ) was used qua monomer, pentaerythritol triacrylate (PETRA) or Divinylbanzene (DVB) was used qua a cross-linker while benzoyl peroxide (BPO) was used as an initiator. The MIP membranes and the membranes of NIP were created by using Dibutyl Sebacate (DBS) and Tris(2-ethylhexyl)phosphate(TEHP) qua plasticizers in PVC matrix. The response time of the liquid electrodes was 1min. whereas their slopes and detection limits reached to 19.62 – 57.36 mV per decade and 1.2 x 10-6 – 2.0 x 10-5 M, respectively. Filling with standard solution of drug (0.1M), the liquid electrodes response -with suitable No.( selectivity for numerous of species - was suitable No.( since pH reached to 1.5 – 12. The developed electrodes were successfully applied for the analyte determination in preparation pharmaceutical sample without any time consuming pretreatment steps.